Cancer in the Himalayas: A Study of Gastrointestinal Malignancies in the Himalayan Population - Thakur, Vikrant; Chauhan, Arun; Patial, Tushar (Nepalese Journal of Cancer, 2025)
This study provides a detailed look at the different types of gastrointestinal cancers diagnosed and treated at Indira Gandhi Medical College (IGMC), Shimla, between August 2018 and August 2020. The research focuses on demographic characteristics, incidence rates, sex distribution, and treatment modalities of patients from Himachal Pradesh, a region characterized by unique climatic, dietary, and socio-economic factors. A total of 410 patients with biopsy-proven gastrointestinal malignancies were analysed, revealing colorectal cancer as the most prevalent (39.5%), followed by gastric cancer (36.1%), hepatobiliary cancer (11.7%), oesophageal cancer (10.7%), and small intestinal cancer (1.0%). The mean age of patients was 56.29 years, with a male predominance (60.5%). Statistical analysis revealed significant findings regarding age distribution and sex ratios across different malignancies. This study highlights the importance of focused cancer awareness and screening programs in the Himalayan region to address the increasing number of gastrointestinal malignancies.